Evaluation of Health Promotion Implementation at General Ahmad Yani Hospital, Metro City - Fansuri, Muhaimin; Setiaji, Bambang; Karyus, Aila; Budiati, Endang; Rolia, Eva; Irawan, Hengki (Miracle Journal of Public Health, 2024)
The implementation of health promotion in hospitals faces various obstacles, one of which is the passive attitude of hospitals that only wait for patients to come without paying attention to health aspects in the surrounding environment. This study evaluates the suitability of implementing standards I, II, III, and IV of Hospital Health Promotion (PKRS) at RSUD Jenderal Ahmad Yani Metro City. The study used a qualitative approach with descriptive methods and involved eight informants. Data were collected through in-depth interviews, observation, and documentation. The results showed that the implementation of PKRS regulations at RSUD Jenderal Ahmad Yani has yet to reach the optimal level. Standard I has yet to be met due to the lack of regulation related to CHAP in the Hospital Strategic Plan (Renstra). In standard II, no health promotion needs assessment has been conducted for various related parties. Meanwhile, in standard III, health promotion interventions have been carried out well for patients and families, although there are still areas for improvement in interventions for hospital human resources. Standard IV shows that monitoring and evaluation have yet to be implemented consistently. Implementing the PKRS regulation at RSUD Jenderal Ahmad Yani still requires improvement to reach the optimal level.